RELASI KIAI DAN PENGUASA DI SURAKARTA - Gusmian, Islah (SUHUF, 2017)
This article studies QurÃ¢â‚¬â„¢an manuscript of Popongan Islamic Boarding school, in Klaten, Central Java. This QurÃ¢â‚¬â„¢an manuscript is studied in the socio-political context of Surakarta in the 19th century AD. There are three main aspects being studied, namely: 1) art aspect (illumination and calligraphy (khaÃ¡Â¹ÂÃ¡Â¹Â), 2) QurÃ¢â‚¬â„¢anic sciences (rasm, qirÃ„ÂÃ¢â‚¬â„¢ah and tajwÃ„Â«d), and 3) socio-political context (the possession of manuscript and the relationship between local Islamic religious leader known as kiai and the ruler of the Surakarta Palace. These three aspects are studied by using codicological approach and Mohammad ArkounÃ¢â‚¬â„¢s historical theory. To be seen from the aspect of QurÃ¢â‚¬â„¢anic sciences, this article shows that the manuscript of Popongan is written by using rasm imlÃ„ÂÃ¢â‚¬â„¢i and qirÃ„ÂÃ¢â‚¬â„¢ah Ã¢â‚¬ËœÃ„â‚¬Ã¡Â¹Â£im which is widely used in the Archipelago. To be seen from the art aspect, the Popongan manuscript is estimated to have come from Terengganu, Malaysia. This conclusion is referred to the character of illumination and the art of writing (khaÃ¡Â¹ÂÃ¡Â¹Â) being used. To be seen f rom the aspect of social history, the existence of the Popongan manuscripts is a trace of the role of Muslims in the Surakarta palace in the era of Pakubuwono X. The owner of the manuscript is Raden Mas Tumenggung (RMT) Wiryadiningrat (d. 1917). He held official position at the Surakarta palace and also was an activist of the Islamic politic and social movement in Surakarta.